Cognitive impairment and depression in Egyptian patients with noncirrhotic chronic hepatitis C virus infection. Issue 1 (January 2015) - Abdel-Mageed, Mahmoud O.; Radwan, Doaa N.; Abd El-Bary, Sameh A.; El-Desouky, Eman D.
Abstract : Background: Patients with chronic hepatitis C virus (HCV) infection have neuropsychiatric and cognitive problems, leading to impairment of quality of life. Aim: The aim of the study was to assess the prevalence of psychiatric morbidity, cognitive impairment, and depression in a group of Egyptian patients with chronic HCV infection. Participants and methods: A total of 150 chronic HCV infection noncirrhotic Egyptian patients were enrolled. Mental health, cognitive functions, and depression were assessed using General Health Questionnaire, mini-mental state test, and BDI-II questionnaire respectively. Results: The study included 82 (54.67%) male patients and 68 (45.33%) female patients with mean age of 40.5±10.74 years. In all, 73 (48.67%) patients had current psychiatric morbidity, 61 (40.67%) patients were suffering from depression, whereas 24 (16%) patients had cognitive impairment. Depression was associated with younger age ( P <0.001), higher education ( P =0.003), and being single ( P =0.048). Cognitive impairment was higher with age ( P <0.001), noneducation ( P <0.001), and with higher liver disease activity ( P <0.001). Regression analysis showed that age had the highest value of predicting depression. Meanwhile, liver activity ( P <0.001), education ( P <0.001), and age ( P =0.007) had the highest values to predict cognitive impairment. Patients with high liver disease activity hold 66 times more to develop cognitive impairment (odds ratio=66). Conclusion: Cognitive impairment is associated with HCV noncirrhotic Egyptian independently from depression. Cognitive impairment is related to higher liver disease activity, which is helpful in providing appropriate health services planning which is necessary in such a prevalent health problem in Egypt.